Plasma conditions for improved energy coupling into the gain region of the Ni-like Pd transient collisional x-ray laser - Marconi, M. C., author; Hunter, J. R., author; Rocca, Jorge J., author; Shlyaptsev, V. N., author; Keenan, R., author; Nilsen, J., author; Moon, S., author; Filevich, J., author; Dunn, J., author; Smith, R. F., author; American Physical Society, publisher (Colorado State University. Libraries, 2005)
We have directly probed the conditions in which the Ni-like Pd transient collisional x-ray laser is generated and propagates by measuring the near-field image and by utilizing picosecond resolution soft x-ray laser interferometry of the preformed Pd plasma gain medium. The electron density and gain region of the plasma have been determined experimentally and are found to be in good agreement with simulations. We observe a strong dependence of the laser pump-gain medium coupling on the laser pump parameters. The most efficient coupling occurs with the formation of lower density gradients in the preformed plasma and when the duration of the main heating pulse is comparable to the gain lifetime (~10 ps for mid-Z Ni-like schemes). This increases the output intensity by more than an order of magnitude relative to the commonly utilized case where the same pumping energy is delivered within a shorter heating pulse duration (<3 ps). In contrast, the higher intensity heating pulses are observed to be absorbed at higher electron densities and in regions where steep density gradients limit the effective length of the gain medium.